On Lactococcus lactis UL719 competitivity and nisin (Nisaplin®) capacity to inhibit Clostridium difficile in a model of human colon - Le Lay, Christophe; Fernandez, Benoit; Hammami, Riadh; Ouellette, Marc; Fliss, Ismail (Frontiers in Microbiology, 2015)
Clostridium difficile is the most frequently identified enteric pathogen in patients with nocosocomially acquired, antibiotic-associated diarrhea and pseudomembranous colitis. Although metronidazole and vancomycin were effective, an increasing number of treatment failures and recurrence of C. difﬁcile infection are being reported. Use of probiotics, particularly metabolically active lactic acid bacteria, was recently proposed as an alternative for the medical community. The aim of this study was to assess a probiotic candidate, nisin Z-producer Lactococcus lactis UL719, competitivity and nisin (Nisaplin®) capacity to inhibit C. difficile in a model of human colon. Bacterial populations was enumerated by qPCR coupled to PMA treatment. L. lactis UL719 was able to survive and proliferate under simulated human colon, did not alter microbiota composition, but failed to inhibit C. difficile. While a single dose of 19 µmol/L (5× the MIC) was not sufficient to inhibit C. difficile, nisin at 76 µmol/L (20× the MIC) was effective at killing the pathogen. Nisin (at 76 µmol/L) caused some temporary changes in the microbiota with Gram-positive bacteria being the mostly affected. These results highlight the capacity of L. lactis UL719 to survive under simulated human colon and the efficacy of nisin as an alternative in the treatment of C. difficile infections.